2015
DOI: 10.1007/s12035-015-9319-7
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Contribution of Vascular Alterations and Aging to Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease characterized by cognitive decline that afflicts as many as 45 % of individuals who survive past the age of 85. AD has been associated with neurovascular dysfunction and brain accumulation of amyloid-β peptide, as well as tau phosphorylation and neurodegeneration, but the pathogenesis of the disease is still somewhat unclear. According to the amyloid cascade hypothesis of AD, accumulation of amyloid-β peptide (Aβ) aggregates initiates a sequence of events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 199 publications
(242 reference statements)
2
47
1
2
Order By: Relevance
“…Furthermore, upregulation of vasoconstrictors would by definition decrease local blood volume as was found in this study. The lower blood volume may be further explained by a lower vascular density which has also been found in AD (Janota et al, 2015).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, upregulation of vasoconstrictors would by definition decrease local blood volume as was found in this study. The lower blood volume may be further explained by a lower vascular density which has also been found in AD (Janota et al, 2015).…”
mentioning
confidence: 66%
“…Adding age as a confounder also did not change the correlation, which shows that increased BBB leakage due to age or partial volume effects caused by atrophy cannot explain the observed link between hypoperfusion and BBB leakage. Together, this all points toward a complicated progressive cascade of events that involves decreased CBF, BBB leakage and inflammation (Janota et al, 2015). Although the precise pathways remain to be elucidated, the correlation between hypoperfusion and increased BBB leakage does fit to the hypothesized positive feedback loop linking the BBB and M A N U S C R I P T…”
mentioning
confidence: 98%
“…LPS and E coli K99 pili protein in vessels and ependymal cells could contribute to vessel injury 29 and ependymal injury 17 and WM injury observed in AD brains. There was more K99 pili protein in GM and WM of AD brains, and both WM and GM are consistently damaged in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, disruptions in cholinergic neurotransmission are known to exacerbate cognitive impairments in pre-clinical AD (Lim et al, 2015). Compared to age-matched control subjects, AD patients exhibited greater blood brain barrier disruption (Erickson and Banks, 2013) and elevated expression of receptor for advanced glycation endproducts (RAGE) (Janota et al, 2016), which is essential for the influx of peripheral Aβ into the brain. Decreased expression of the efflux receptor for Aβ, lipoprotein receptor-related protein (LRP)-1 and increased influx receptor RAGE (Silverberg et al, 2010a; Silverberg et al, 2010b) has been reported in AD brains, which would be expected to enhance intracellular accumulation Aβ.…”
Section: Aging Of White Matter In Neurodegenerative Diseasesmentioning
confidence: 99%